Quinazolinone and Quinazoline Derivatives - Gamal Al-kaf, Ali (IntechOpen, 2020)
One of the problems with modern public health is target searching for new highly effective medicinal preparations. Among those medicinal preparations are the natural and synthetic origins of quinazolinone-4 derivatives. Quinazolinone derivatives are reported to be physiologically and pharmacologically active. They also exhibit a wide range of activities such as anticonvulsant, antiinflammatory, antifungal, antimalarial, and sedative properties. Some of these compounds are identified as drugs used as diuretics, vasodilators, and antihypertensive agents. Moreover, sulfonamide derivatives have been widely used as bacteriostatic agents. Prompted by the above-mentioned facts and in conjunction with our ongoing program on the utility of readily obtainable starting material for the synthesis of heterocyclic systems of biological interest, we have decided to synthesize a series of quinazolinone derivatives having sulfonamide moiety with a potentially wide spectrum of biological responses.